PENGARUH BIMBINGAN BELAJAR TERHADAP MOTIVASI BELAJAR SISWA DI SEKOLAH DASAR - Ramlah Ramadhani.Ns; Perawati Bte Abustang; Eka Fitriana HS; R.Supardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of tutoring on elementary school students' learning motivation. The research method used is quantitative research using correlational methods. The population was all 88 fifth-grade students at SD Inpres Perumnas Antang 3, with a sample size of 60 students selected using simple random sampling. The research instrument consisted of a questionnaire on tutoring and student learning motivation, which was tested for validity and reliability. Data analysis used the Pearson product-moment correlation test with the help of SPSS. The results showed a significant effect of tutoring on student learning motivation. The correlation coefficient (r) was 0.812 with a significance level of 0.000 < 0.05, indicating a very strong and significant relationship between the two variables. The coefficient of determination (R²) of 0.659 indicates that tutoring contributed 65.9% to the variation in student learning motivation, with the remainder influenced by factors outside the study. Therefore, it can be concluded that tutoring positively contributes to improving elementary school students' learning motivation.